Risk-taking decision on sales performance of Micro-small businesses in Douala's V - Forji, Efeutlancha Angelus; Aloysius, Njong Mom; Felix, Nkiendem (goodwood publishing, 2025)
Purpose: This research aimed to investigate the effect of risk-taking on the sales performance of micro and small enterprises in Douala V, Cameroon. Research Methodology: This study employed a quantitative research design, utilising a questionnaire as the primary data collection instrument. A sample of 385 MSEs who participated in the study , and the sample size was selected using simple random sampling techniques. The collected data were analysed using the ordinary least squares technique (OLS) with the help of STATA 17. Results: The finding reveals a positive and significant effect between risk-taking and sales performance in micro and small-sized enterprises in Douala V, Cameroon Age of the entrepreneur and Longevity of business were found to significantly affect sales performance. Conclusions: The study highlights the benefits of taking risks for sales performance MSE and the significance of providing younger entrepreneurs with specialized support. Limitations: The study is limited to micro and small-sized enterprises in Douala's five municipality, thus making the generation of results difficult. Contribution: The study provides insightful policy implications for micro and small-sized enterprises operating with limited resource capacity, The policy will be useful to newly created NGOs and Government Stakeholders.